2015
DOI: 10.1038/jcbfm.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Translocation of Soluble Epoxide Hydrolase Protects against Ischemic Stroke Injury

Abstract: Soluble epoxide hydrolase (sEH) contributes to cardiovascular disease, including stroke, although the exact mechanism remains unclear. While primarily a cytosolic enzyme, sEH can translocate into peroxisomes. The relevance of this for stroke injury is not understood. We tested the hypothesis that sEH-mediated injury is tied to the cytoplasmic localization. We found that a human sEH variant possessing increased affinity to peroxisomes reduced stroke injury in sEH-null mice, whereas infarcts were significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Compartmentalization within specific organelles may similarly be important to EH function. For example, the peroxisomal sEH has been suggested to have a different role than the cytosolic sEH [ 42 ]. Future experiments on cultured cells or whole isolated tissues, where cell and tissue structure are preserved, may serve as a bridge between the in vitro observations in tissue homogenates and translation to human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentalization within specific organelles may similarly be important to EH function. For example, the peroxisomal sEH has been suggested to have a different role than the cytosolic sEH [ 42 ]. Future experiments on cultured cells or whole isolated tissues, where cell and tissue structure are preserved, may serve as a bridge between the in vitro observations in tissue homogenates and translation to human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This role for sEH would be consistent with the protection from ischemia afforded by R287Q human polymorphism [ 5 , 6 ]. Indeed, the a recent publication has suggested that soluble epoxide hydrolase localized to peroxisomes is protective in ischemia [ 16 ]. This action may be protective through two independent mechanisms; 1) sequestration of the enzyme away from EETs in the cytosol thereby elevating levels of this protective molecule and 2) detoxification of fatty acid epoxides in dysfunctional peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important cell type to understand the mechanism of sEH subcellular distribution given previous studies identifying sEH as a stroke risk factor [ 3 , 13 ]. Furthermore, two mouse studies have suggested that the subcellular distribution of sEH within neurons is linked to the degree of damage in ischemic injury [ 6 , 14 ]. Therefore, we set out to directly test the hypothesis that dimerization regulates the subcellular distribution of sEH in primary neuronal culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian sEH is localized to both the cytosol and peroxisomes (Gill, Grant et al, 1994). A previous study indicated sEH contributes to stroke injury only when localized in the cytoplasm, while peroxisomal sEH may be protective, showing the different biological functions of cytosolic and peroxisomal sEH (Nelson, Zhang et al, 2015). Interestingly, the human sEH is located in both cytosolic and peroxisomal compartments in hepatocytes and renal proximal tubules, while sEH is exclusively located in cytosolic compartment in other sEH-containing tissues such as pancreatic islet cells, intestinal epithelium, and anterior pituitary cells.…”
Section: Introductionmentioning
confidence: 99%